Maximum likelihood fitting of acyclic directed mixed graphs to binary data - Evans, R; Richardson, T (2010)
Acyclic directed mixed graphs, also known as semi-Markov models represent the conditional independence structure induced on an observed margin by a DAG model with latent variables. In this paper we present the first method for fitting these models to binary data using maximum likelihood estimation.